Paleoproterozoic UHT metamorphism in the Daqingshan Terrane, North China Craton: New constraints from phase equilibria modeling and SIMS U-Pb zircon dating - Jiao, Shujuan; Fitzsimons, Ian; Guo, J. (Elsevier BV, 2017)
The P-T-t path and tectonic setting of Paleoproterozoic UHT metamorphism in the Khondalite Belt of the North China Craton are controversial, but important new constraints are provided by phase equilibria modeling and SIMS U-Pb dating of Grt-Sil-Spl-Spr granulites from the Dongpo locality. These metapelitic granulites are composed of garnet, sillimanite, plagioclase, biotite, spinel, sapphirine, rutile, ilmenite, and rare cordierite, but lack quartz and K-feldspar. Such refractory whole-rock compositions indicate that the Dongpo granulites had undergone high-grade metamorphism and substantial melt loss prior to peak UHT conditions. Four metamorphic stages are recognized based on petrography, mineral chemistry and reaction analysis. The earliest M1 stage is recorded by cores (zone 1) of garnet porphyroblasts and coarse-grained plagioclase, sillimanite, biotite and spinel in the matrix. This was overprinted by the M2 assemblage comprising the mantles (inner zone 2) of garnet porphyroblasts, Spr±Spl+Pl intergrowths, and sapphirine coronas that surround spinel, and then by the development of Sil+Bt and outermost zone 2 of Grt3 (M3) and minor Crd+Ilm (M4). Pseudosections calculated for different effective bulk compositions constrain the P-T conditions of M1 to ca. 9.0-10.0kbar and 850-920°C, and M2 to 7.3-9.0kbar and 910-1020°C. If M1-M4 assemblages developed during a single tectonic cycle, these results define a clockwise P-T path comprising M1-M2 decompression heating, followed by M2-M4 cooling and decompression. SIMS U-Pb analysis reveals three generations of metamorphic zircon that show evolving HREE contents consistent with zircon crystallization during or after garnet growth. A poorly defined zircon population at ca. 1.94-1.90Ga is ascribed to pre- to syn-M1 metamorphism, while ca. 1.85Ga and =1.82Ga zircon are linked to post-UHT M2-M3 and M3-M4 retrogression respectively. These age data suggest a minimum 50Myr duration for high-T to UHT metamorphism, consistent with prolonged radiogenic heating in thickened crust, provided that M1 and M2 are part of a single tectonic cycle in which case they are likely to reflect collision and extension respectively. Alternatively, M1 and M2 might be unrelated events, with M2 UHT metamorphism linked to mantle-derived magmatism at least ca. 50Myr after M1 collisional orogenesis.